PERCENTAGE OF ELIGIBILITY OF BALI CATTLE LIVER (BOS SONDAICUS) DURING THE 2025 EID AL-ADHA THROUGH POSTMORTEM EXAMINATION IN DANGIN PURI KELOD VILLAGE, DENPASAR CITY - Irmawan, Adi; Mufa, Romy Muhammad Dary; Ardana, Ida Bagus Komang (Buletin Veteriner Udayana, 2026)
The celebration of Eid al-Adha as sacrificial worship is closely related to aspects of animal health and the safety of animal-derived food, as its implementation requires compliance with animal health and welfare principles, as well as assurance of meat suitability for public consumption. The increasing number of sacrificial animals each year necessitates greater attention to animal health to ensure food safety for the community. The liver of Bali cattle (Bos sondaicus) is an important indicator of the overall health of the body. This study aimed to determine the percentage of suitability of Bali cattle livers from sacrificial animals during Eid al-Adha through postmortem examination in Dangin Puri Kelod Village, East Denpasar District, Denpasar City, Indonesia. The study employed an observational method with a cross-sectional study design, involving 28 Bali cattle liver samples (total sampling). Examinations were conducted using inspection, palpation, and incision methods, with assessment parameters including color, shape, consistency, odor, and lesions. The results showed that 27 samples (96%) were normal and suitable for consumption, while one sample (4%) was abnormal and deemed unfit for consumption. These findings indicate that the majority of sacrificial Bali cattle livers in Dangin Puri Kelod Village met the ASUH standards (Safe, Healthy, Wholesome, and Halal). Continuous post-mortem examinations are necessary to ensure food safety and protect public health.